A Case Study of Entrepreneurial Skills of Higher Education Graduates in an Islamic College in Malaysia - Zuraina, Ali; Hasmadi, Hassan; Noor Raha, Mohd Radzuan; Aswahida, Sabaruddin; Mohd Hafiz, Yaakub; Nurizan, Baharum; Nurulhuda, Othman; Shafinas, Sharifuddin; Siti Mariam, Sakari (UMP Press, 2016)
The purpose of the paper is to explore entrepreneurial skills of higher education graduates; specifically the Islamic college graduates in Pahang concerning their entrepreneurial skills. Interviews were conducted with ten (10) employers from various fields to gauge their perceptions, expectations and hiring opportunity of the Islamic college graduates in relation to the skills. Findings from the study derived from the qualitative data has generated four themes that are entrepreneurial skills are individual interest, entrepreneur non-friendly practices, nil opportunity for entrepreneurship and employee’s entrepreneurial motivation. The study implies that communicating the idea to develop entrepreneurial skills among graduates demand conscientious strategies from educators. Though the skills are individual pursuit, the opportunity from employers is also a significant factor in determinining whether or not graduates can build the interest.